2020
DOI: 10.1017/s1446181120000103
|View full text |Cite
|
Sign up to set email alerts
|

Critical Length for the Spreading–vanishing Dichotomy in Higher Dimensions

Abstract: We consider an extension of the classical Fisher–Kolmogorov equation, called the “Fisher–Stefan” model, which is a moving boundary problem on $0<x<L(t)$ . A key property of the Fisher–Stefan model is the “spreading–vanishing dichotomy”, where solutions with $L(t)>L_{\text{c}}$ will eventually spread as $t\rightarrow \infty$ , whereas solutions where $L(t)\ngtr L_{\text{c}}$ will vanish as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Equations (32)- (37) are solved numerically using a boundary fixing transformation [44]. In doing so, Equations 32…”
Section: Continuum Modelmentioning
confidence: 99%
“…Equations (32)- (37) are solved numerically using a boundary fixing transformation [44]. In doing so, Equations 32…”
Section: Continuum Modelmentioning
confidence: 99%
“…Du and Lin 16 refer to this situation as the spreading‐vanishing dichotomy. Aspects of these phenomena have been studied rigorously and numerically by Du and coworkers, 16,28–31,50 us, 27,46–49 and others.…”
Section: Discussionmentioning
confidence: 99%
“…In very recent times, a variety of extensions have been documented, including a rigorous results for different boundary conditions, nonlinear or nonlocal diffusion, generalized reaction terms, with one or two phases, as well as motivation in terms of applications in ecology 32–45 . Formal results and numerical simulations have been described by us 27,46–49 and others 50 …”
Section: Introductionmentioning
confidence: 99%
“…Simpson [42] extended the work of Du and Lin [37] by considering the Fisher-Stefan model on an n-sphere. By replacing the second derivative term in (1.4a) with the ndimensional radially-symmetric Laplacian operator, Simpson [42] showed that a critical radius, R c , governs survival and extinction analogously to the critical length.…”
Section: Introductionmentioning
confidence: 99%
“…Simpson [42] extended the work of Du and Lin [37] by considering the Fisher-Stefan model on an n-sphere. By replacing the second derivative term in (1.4a) with the ndimensional radially-symmetric Laplacian operator, Simpson [42] showed that a critical radius, R c , governs survival and extinction analogously to the critical length. This critical radius depends on the dimension n. In the two-dimensional spreading-disc problem, the critical radius is R c = α 01 ≈ 2.4048, where α 01 is the first zero of J 0 (x), the zeroth-order Bessel function of the first kind [42].…”
Section: Introductionmentioning
confidence: 99%